Zarządzanie personelem - doświadczenia finalistów Polskiej Nagrody Jakości - Rogala, Piotr (Staff Management - Experience of the Finalists of the Polish Quality Award, 2008)
The aim of the article is to assess the accomplishment extent of the staff management in Polish organizations oriented to TQM.. To achieve this goal, an experience analysis of twelve chosen Polish Quality Award's finalists was performed. On this basis conclusions and recommendations concerning further research in the area were formed. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 569-574